EDUKASI PERSONAL HYGIENE PADA REMAJA DI PULAU PANJANG KECAMATAN GALANG - Andolina, Nuari; Amir, Eka Fitri; Riskia, Anisa (Awal Bros Journal of Community Development, 2023)
Adolescent reproductive health is a healthy condition that concerns the reproductive system, functions and processes possessed by adolescents. Personal hygiene or poor personal hygiene can increase the risk of infection which can result in the emergence of various diseases, especially in adolescent children. To improve individual health status, it is necessary to make efforts to improve personal hygiene behavior with the end result of reducing the morbidity of infectious diseases. School-age children, from an early age to their teens, still often neglect personal hygiene. As a result of poor personal hygiene can increase the risk of infection which can result in the emergence of various diseases. For this reason, health-related behaviors must be applied to children as early as possible. Providing an understanding of adolescents is very important so that awareness arises about the importance of maintaining health. The targets for this activity were teenagers on Panjang Island, Galang District. The method of carrying out this activity is counseling which provides direct education, question-and-answer, and evaluation through posttest and pretest. This activity was held on June 10 2023 on Pulau Panjang, Galang District and was attended by 30 youth. The result of this activity is an increase in knowledge about personal hygiene in adolescents on Panjang Island, Galang District